(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
The article is devoted to the study of the semantics and syntactics of prepositions in verbs of movement in the Russian language, as well as to the analysis of typical problems of interpretation faced by students of non-linguistic universities in the process of learning Russian as a foreign language. Special attention is paid to the semantic features of prepositions that define spatial-temporal and causal relationships, as well as their interaction with verbs of movement. The relevance of the study is due to the fact that prepositions in verbs of movement represent a significant difficulty for students whose native languages have a different grammatical structure. The article examines the causes of difficulties, such as the lack of analogues in the native languages of students, the complexity of the semantic perception of prepositions and their ambiguity. In the course of the work, typical mistakes of students are analyzed, key problem areas are identified and ways to eliminate them are proposed. To study the peculiarities of the interpretation of prepositions, methods of observation, questioning and analysis of written and oral works of students were used. Methodological approaches that can be used to improve the understanding and use of prepositions in verbs of movement, including communicative and interactive exercises, are also considered. The results of the study are of practical importance for teachers of Russian as a foreign language who develop educational materials and methodological recommendations for students of non-linguistic universities. The solutions proposed in the article are aimed at improving the grammatical competence of students and overcoming interlanguage barriers, which ultimately contributes to a deeper development of the Russian language.